Disclosure of Sustainability Reporting, Corporate Governance Perception Index and Their Effect on Corporate Financial Performance (Empirical Study of Companies Participating in CGPI Reporting & Listing on the Indonesia Stock Exchange 2016-2020) - Bambang Subiyanto; Rizkika Ariestantya Sujana (Budapest International Research and Critics University, 2022)
Sustainability reporting can build interest in shareholders with a long-term vision and help demonstrate how to increase company value in terms of social and environmental issues. The purpose of this study was to determine the effect of the disclosure of sustainability reporting, corporate governance perception index on financial performance. The financial performance variable as measured by the return on assets of the companies participating in the 2016-2020 Corporate Governance Perception Index. The amount of data in this study were 61 companies with 8 companies being the research sample, and the total number of observations was 40. Types of data in this study is secondary data obtained from the Indonesian stock exchange and the official website of each company. Data collection in this study used purposive sampling technique. The analysis technique used is multiple linear regression analysis. Data processing using SPSS 25. The results of the study show that sustainability reporting and corporate governance perception index have an effect on financial performance.